Inter-annual changes in oceanic conditions drives spatial and trophic consistency of a tropical marine predator. (December 2020) - Cerveira, L.R.; Ramos, Jaime A.; Rodrigues, Isabel; Almeida, Nathalie; Araújo, Pedro M.; Santos, Ivo dos; Vieira, Cristiana; Pereira, Jorge M.; Ceia, Filipe R.; Geraldes, Pedro; Melo, Tommy; Paiva, Vitor H.
Abstract: Pelagic seabirds exhibit plasticity in foraging characteristics in relation to oceanographic conditions. This should be particularly relevant in tropical marine environments where food resources are naturally more unpredictable. We studied how inter-annual variations (2013–2018) in tropical oceanographic conditions (driver of oceanic productivity) can influence the spatial and trophic ecology of Cape Verde shearwater ( Calonectris edwardsii) during the breeding season. During years of poor oceanographic conditions around the colony, birds engaged in longer trips to West Africa, showed higher spatial and behavioural consistency, and presented a wider isotopic niche. Opposite patterns were generally found for years of good oceanographic conditions, when birds foraged more on their colony surroundings. New foraging areas off West Africa were highlighted as relevant, especially during years of poor environmental conditions. This study highlights the need for long-term studies to assess variation in foraging areas and foraging decisions by seabird populations. Highlights: Despite shifts in oceanographic conditions C. edwardsii showed foraging consistency. Under poor oceanographic conditions birds increased their spatial consistency. New foraging hotspots off West Africa were highlighted during this 6-year study. This key information should support an informed design of MPAs in this tropical area.